2021
DOI: 10.1007/s00702-021-02359-3
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of psychobiological stress regulation with valence and quantity of social interactions in everyday life: disentangling intra- and interindividual sources of variation

Abstract: While the overall effects of social relationships on stress and health have extensively been described, it remains unclear how the experience of social interactions covaries with the activity of psychobiological stress in everyday life. We hypothesized that the valence as well as quantitative characteristics of social interactions in everyday life would attenuate psychobiological stress. Sixty healthy participants provided data for the analyses. Using an ecological momentary assessment design, participants rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Another study on a healthy study population measuring acute stressor severity during social interactions and cortisol concurrently found no association [ 85 ]. Other studies using longer time lags between acute stressor severity during social interactions [ 82 , 86 ] or using a study population with autism spectrum disorders [ 87 ] also found no association. Regarding severity of acute stressors at work, cortisol levels were positively associated with concurrent measurement of the ability to meet work demands [ 88 ] and with performance pressure [ 89 ] but not with task failure measured for periods up to one hour preceding cortisol sampling.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Another study on a healthy study population measuring acute stressor severity during social interactions and cortisol concurrently found no association [ 85 ]. Other studies using longer time lags between acute stressor severity during social interactions [ 82 , 86 ] or using a study population with autism spectrum disorders [ 87 ] also found no association. Regarding severity of acute stressors at work, cortisol levels were positively associated with concurrent measurement of the ability to meet work demands [ 88 ] and with performance pressure [ 89 ] but not with task failure measured for periods up to one hour preceding cortisol sampling.…”
Section: Resultsmentioning
confidence: 96%
“…Spinal cord injury [ 79 ], high coping efficacy and engagement coping in general [ 78 ] were related to decreased stress reactivity. Whereas one study examining pregnant women [ 80 ] and one study examining working adults [ 81 ] found positive relationships between global subjective stress and current cortisol levels, other studies with working adults [ 82 ] and women with fibromyalgia [ 83 ] found no such association. Furthermore, one study among healthy adults suggests that several subjective responses to stress attenuate a positive effect of global subjective stress on momentary cortisol levels [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other measures that cannot be computed using mobility data may be more useful to highlight day-to-day variability in behaviours. For example, day-to-day variation for a number of social interaction measures and a greater number of quality daily social contacts have been associated with lower subjective stress ( Stoffel et al, 2021 ). Suggesting further research and studies designs are required that combine mobility metrics and social interaction measures.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, momentary assessment studies are highly qualified to examine short to medium term fluctuations and interactions. In their study employing such a design, Stoffel and colleagues (Stoffel et al 2021) show ecologically valid evidence for direct attenuating effects of social interactions on psychobiological stress. Using an experimental approach, on the other hand, Denk et al (2021) examined the phenomenon of physiological synchrony between study participants; they found both cortisol and alpha-amylase physiological synchrony in participants who were in the same group while being exposed to a stressor.…”
mentioning
confidence: 99%